OPTIMIZING EARLY DIAGNOSIS OF CHRONIC GLOMERULONEPHRITIS THROUGH GENETIC SCREENING (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Chronic kidney disease occurs in 80-90% of patients with chronic glomerulonephritis. Despite advances in treatment in recent years, the risk of death remains high in patients with chronic kidney disease. Early detection and treatment of kidney damage in chronic glomerulonephritis reduces the risk of irreversible inflammation in the kidneys and is important for preserving kidney function. In this methodological recommendation, the groups of patients with nephrotic and mixed clinical forms of chronic glomerulonephritis were compared according to the results of laboratory and instrumental examination. Early detection of kidney damage by checking a number of indicators that are markers of kidney damage and early treatment improves the patient's quality of life and prolongs the patient's life expectancy.